PENINGKATAN MINAT, MOTIVASI DAN KESIAPAN BERWIRAUSAHA MASYARAKAT PEDUKUHAN NGRUNGGO, DESA GETAS, KECAMATAN PLAYEN, KABUPATEN GUNUNGKIDUL - Rubiyatno, Rubiyatno; Sutadi, Theodorus; Adinata, Patrick Vivid; Yulita, Ima Kristina (Jurnal Pengabdian dan Kewirausahaan, 2020)
Ngrunggo vilage has abundant natural resources in the form of agricultural products namely cassava and corn. However, this potential has not been able to optimally increase the income of citizens. The women villager in the village already have sufficient skills to produce processed products from cassava. However, they still feel hesitant to develop the cassava chip business seriously. This community service aims to provide insight about entrepreneurship, as well as generate interest, motivation and increase entrepreneurship readiness for women villagers on Ngrunggo, Getas village, Playen district, Gunung Kidul regency. The method used is group counseling or group approach that is a counseling that is related to the target group counseling. The results of this service show that participants have an adequate interest, motivation and entrepreneurial readiness to run a business. Although the interests, motivations and readiness are still in the form of attitude, not in the form of action.